A scoping review of powered wheelchair driving tasks and performance-based outcomes. - Bigras, Catherine; Owonuwa, Dolapo D.; Miller, William C.; Archambault, Philippe S. (Disability & Rehabilitation: Assistive Technology, 2020)
Introduction: Wheelchairs and scooters promote participation and have positive effects on quality of life. However, powered wheelchairs (PW) use can be challenging and can pose safety concerns. Adequate PW assessment and training is important. There is a wide variety of tasks and PW driving assessment measures used for training and assessing PW driving ability in the literature and little consensus as to which tasks and outcomes are the most relevant. A scoping review of the literature was performed in order to characterize this extensive variety of tasks and performance-based outcomes used for training and assessing PW skills. Methods: A search of the literature was conducted in January 2017. Four databases were searched: CINAHL, Embase, PsycInfo and Medline. Articles were included if they contained at least one PW driving task. Results: 827 articles were screened and 48 articles were retained. PW driving tasks from each article were identified and categorized in terms of the environment in which they were performed: Driving in a controlled environment, ecological driving tasks, 2D virtual environment (VE) tasks, 3D VE tasks. The assessment measures formed a separate category. Subjective and objective performance-based outcomes related to PW driving were also identified and grouped into outcomes assessing speed and outcomes assessing accuracy. Conclusion: This scoping review provides an overview of tasks and performance outcomes used in the literature when training and assessing PW skills. The results of this review could guide future research when choosing appropriate tasks and performance outcomes for PW driving ability. There is wide variety of tasks and performance-based outcomes for PW driving. Results showed that available assessment measures are not commonly used in research and that tasks used often lacked consistency across studies. New methods to measure the interaction of speed and accuracy are needed. The contents of this review could be used by researchers as a starting point when designing a PW task and selecting appropriate performance-based outcomes.